Qualitative methods in PhD theses from general practice in Scandinavia - Kirsti Malterud; Katarina Hamberg; Susanne Reventlow (Taylor & Francis Group, 2017)
Qualitative methodology is gaining increasing attention and esteem in medical research, with general practice research taking a lead. With these methods, human and social interaction and meaning can be explored and shared by systematic interpretation of text from talk, observation or video. Qualitative studies are often included in Ph.D. theses from general practice in Scandinavia. Still, the Ph.D. programs across nations and institutions offer only limited training in qualitative methods. In this opinion article, we draw upon our observations and experiences, unpacking and reflecting upon values and challenges at stake when qualitative studies are included in Ph.D. theses. Hypotheses to explain these observations are presented, followed by suggestions for standards of evaluation and improvement of Ph.D. programs. The authors conclude that multimethod Ph.D. theses should be encouraged in general practice research, in order to offer future researchers an appropriate toolbox.